A Conceptual Framework for Evaluating Health Equity Promotion within Community-Based Participatory Research Partnerships - Ward, Melanie (Eval Program Plann, 2018)
Community-based participatory research (CBPR) approaches present strong opportunities to promote health equity by improving health within low-income communities and communities of color. CBPR principles and evaluation frameworks highlight an emphasis on equitable group dynamics (e.g., shared leadership and power, participatory decision-making, two-way open communication) that promote both equitable processes within partnerships and health equity in the communities with whom they engage. The development of an evaluation framework that describes the manner in which equitable group dynamics promote intermediate and long-term equity outcomes can aid partners in assessing their ability to work together effectively and improve health equity in the broader community. CBPR principles align with health equity evaluation guidelines recently developed for Health Impact Assessments (HIAs), which emphasize meaningful engagement of communities in decision-making processes that influence their health. In this paper, we propose a synergistic framework integrating contributions from CBPR and HIA evaluation frameworks in order to guide efforts to evaluate partnership effectiveness in addressing health inequities. We suggest specific indicators that might be used to assess partnership effectiveness in addressing health equity and discuss implications for evaluation of partnership approaches to address health equity.